2005
DOI: 10.1126/science.1108423
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Pathogen Reduces Potential for Malaria Transmission

Abstract: Using a rodent malaria model, we found that exposure to surfaces treated with fungal entomopathogens following an infectious blood meal reduced the number of mosquitoes able to transmit malaria by a factor of about 80. Fungal infection, achieved through contact with both solid surfaces and netting for durations well within the typical post-feed resting periods, was sufficient to cause >90% mortality. Daily mortality rates escalated dramatically around the time of sporozoite maturation, and infected mosquitoes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
301
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(316 citation statements)
references
References 17 publications
13
301
0
2
Order By: Relevance
“…The proteins that mediate lipid storage in fungi are still unknown. In this study we show that the ascomycete Metarhizium anisopliae, a ubiquitous insect pathogen and biocontrol agent (8), produces a single mammalian perilipin homolog we designated as Mpl1 for Metarhizium perilipin-like protein. To demonstrate possible conserved functions, we characterized the Mpl1 gene, asked whether its product participates in the regulation of lipid storage, and investigated its influence on fungal processes such as pathogenicity.…”
mentioning
confidence: 99%
“…The proteins that mediate lipid storage in fungi are still unknown. In this study we show that the ascomycete Metarhizium anisopliae, a ubiquitous insect pathogen and biocontrol agent (8), produces a single mammalian perilipin homolog we designated as Mpl1 for Metarhizium perilipin-like protein. To demonstrate possible conserved functions, we characterized the Mpl1 gene, asked whether its product participates in the regulation of lipid storage, and investigated its influence on fungal processes such as pathogenicity.…”
mentioning
confidence: 99%
“…Obligate killing entomopathogenic fungi like the well-known green muscardine disease (Metarhizium anisopliae, Zimmermann (2007)) and white muscardine disease (Beauveria bassiana, Barbarin et al (2012)) are frequently used in biocontrol of pest insects such as, e.g., migratory locusts (Wilson et al, 2002) and mosquitoes (Blanford et al, 2005;Scholte et al, 2005;Thomas and Read, 2007). They are also used against social insects (e.g., termites Almeida et al (1997) and ants (Jaccoud et al, 1999)), which are particularly successful invasive species (Chapman and Bourke, 2001;Cremer et al, 2008) with a high economic burden (Lowe et al, 2000;Pimentel et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Nielsen et al (2005) could detect no genetic variation among Lymantria dispar strains in susceptibility to the fungal pathogen Entomophaga maimaiga and Blanford et al (2005) reported no cases on the evolution of resistance to fungal biopesticides. Variation does exist among pea aphid (Acyrtosiphon pisum) clones in resistance to the fungal pathogen Pandora (Erynia) neoaphidis (Ferrari et al, 2001), although this may be due to differences in the secondary endosymbionts they carry , Ferrari et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal pathogens are used as biopesticides, for example against locusts, while new applications such as combating the mosquito vectors of malaria are being explored (Kooyman et al, 1997;Lomer et al, 2001;Blanford et al, 2005;Scholte et al, 2005). Evolution of resistance against pesticides is a continuing problem in pest control.…”
Section: % Fitness Is Reachedmentioning
confidence: 99%